2018
DOI: 10.1038/s41467-018-03501-8
|View full text |Cite
|
Sign up to set email alerts
|

Engineering enhanced cellobiohydrolase activity

Abstract: Glycoside Hydrolase Family 7 cellobiohydrolases (GH7 CBHs) catalyze cellulose depolymerization in cellulolytic eukaryotes, making them key discovery and engineering targets. However, there remains a lack of robust structure–activity relationships for these industrially important cellulases. Here, we compare CBHs from Trichoderma reesei (TrCel7A) and Penicillium funiculosum (PfCel7A), which exhibit a multi-modular architecture consisting of catalytic domain (CD), carbohydrate-binding module, and linker. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 75 publications
3
70
1
Order By: Relevance
“…From a structural perspective, the entire CtCel7_CD region houses the classical curved β-sandwich constructed with two largely antiparallel β-sheets in an equatorial elongated substrate-binding tunnel, which is in accordance with the archetypal feature of GH7 CBH structures (Figure 2A; Momeni et al, 2014;Borisova et al, 2015). This predominant structural feature allows CtCel7 to act along cellulose chains without affecting the substrate configuration and clip off numerous cellobiose units before detaching from the substrate (Kadowaki et al, 2018), which is indispensable to its prominent hydrolysis efficiency on highly crystalline cellulose (Payne et al, 2015;Taylor et al, 2018). Combined with the homologous sequence alignment, the results identified the catalytic triad residues Glu213 (nucleophile), Asp215 and Glu218 (acid/base) in CtCel7 and revealed that these are embedded in the binding tunnel, where two cellotriose molecules (−5 to −3 and −1 to +2 subsites, respectively) are involved in coordinated interactions with adjacent residues located within 5 Å via hydrogen bonding (Figures 2B,C).…”
Section: Sequence Analysis Of Ctcel7supporting
confidence: 70%
See 1 more Smart Citation
“…From a structural perspective, the entire CtCel7_CD region houses the classical curved β-sandwich constructed with two largely antiparallel β-sheets in an equatorial elongated substrate-binding tunnel, which is in accordance with the archetypal feature of GH7 CBH structures (Figure 2A; Momeni et al, 2014;Borisova et al, 2015). This predominant structural feature allows CtCel7 to act along cellulose chains without affecting the substrate configuration and clip off numerous cellobiose units before detaching from the substrate (Kadowaki et al, 2018), which is indispensable to its prominent hydrolysis efficiency on highly crystalline cellulose (Payne et al, 2015;Taylor et al, 2018). Combined with the homologous sequence alignment, the results identified the catalytic triad residues Glu213 (nucleophile), Asp215 and Glu218 (acid/base) in CtCel7 and revealed that these are embedded in the binding tunnel, where two cellotriose molecules (−5 to −3 and −1 to +2 subsites, respectively) are involved in coordinated interactions with adjacent residues located within 5 Å via hydrogen bonding (Figures 2B,C).…”
Section: Sequence Analysis Of Ctcel7supporting
confidence: 70%
“…The quantification of the substrate preference of the enzyme based on the presence of different glycosidic bonds demonstrated that the bifunctional CtCel7 was most adept in the microcrystalline cellulose depolymerization of PASC and filter paper with values of 2.54 and 2.16 IU/mg, respectively, which were relatively higher than those obtained with the commercial cellobiohydrolase TlCBHI and the commercial xylanase TlXyn. The hydrolysis of crystalline cellulose is the fundamental substrate preference of CBHs and is a central step in cellulose material degradation in natural and industrial settings (Taylor et al, 2018). In addition, CtCel7 exhibited efficient hydrolysis of soluble cellulosic substrates (glucan and CMC-Na), xylan and lichenin.…”
Section: Substrate Specificity Of Ctcel7mentioning
confidence: 99%
“…From a site saturation mutagenesis library of non-catalytic residues near the catalytic site, a 2.7-fold improvement in the catalytic efficiency was obtained and thus, helps us to understand which residues influence the activity of a β-glucosidase [84]. In order to understand more extensively the role of different areas of cellobiohydrolases, Taylor et al exchanged regions with two homologous Cel7A, obtaining molecular insights about the role of the entrance tunnel in the Cel7A activity [85]. Directed evolution (random mutagenesis) has been utilized to improve the activity in different cellulases such as endoglucanases [86], cellobiohydrolases, and β-glucosidases (Table 2) [87,88].…”
Section: Engineering Cellulases For Enhanced Activity For Cellulose Dmentioning
confidence: 99%
“…Improved enzymes exhibiting, e.g. better thermal stability, higher catalytic rate or reduced inhibition have been developed by enzyme screening and engineering (Berlin et al , Percival Zhang et al , Voutilainen et al , Heinzelman et al , , Voutilainen et al , Chokhawala et al , Taylor et al ). High‐throughput sequencing combined with bioinformatic sequence mining tools, heterologous expression and novel substrates and screening methods have been developed for CAZymes (Cragg et al , Deng et al , Vidal‐Melgosa et al ).…”
Section: Enzymatic Processing Of Lignocellulosicsmentioning
confidence: 99%